2018
DOI: 10.1136/bcr-2018-225762
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous bilateral perirenal and splenic haematoma in childhood onset polyarteritis nodosa

Abstract: Spontaneous bilateral perirenal haematoma, as well as splenic haematoma, are rare occasions in polyarteritis nodosa (PAN). We report a case of a young man, who suffered from various typical and atypical manifestations of PAN since childhood. The diagnosis was delayed due to symptoms mimicking with other clinical conditions. Finally, the diagnosis was confirmed when presented with perirenal and splenic haematoma and was managed successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Spontaneous bilateral renal hemorrhage is extremely rare because it is unlikely to occur in the absence of anticoagulant or antiplatelet intake when it occurred consecutively not simultaneously. 14 In our case, the rst event of the renal hemorrhage occurred when the patient took clopidogrel (oral antiplatelet) daily, and the second event of renal hemorrhage occurred only 15 days after the rst hospital discharge.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Spontaneous bilateral renal hemorrhage is extremely rare because it is unlikely to occur in the absence of anticoagulant or antiplatelet intake when it occurred consecutively not simultaneously. 14 In our case, the rst event of the renal hemorrhage occurred when the patient took clopidogrel (oral antiplatelet) daily, and the second event of renal hemorrhage occurred only 15 days after the rst hospital discharge.…”
Section: Discussionmentioning
confidence: 65%
“…[1][2][3][4][5][6][7] In particular, spontaneous bilateral renal hemorrhages accounted for only 3% of all case reports on spontaneous renal hemorrhage, and all cases were PAN. 14 Phillips et al reported that BehÇet's disease and segmental arterial mediolysis may cause spontaneous renal hemorrhage. 4 In our case, a CT scan revealed no sign of tumor or other causes of renal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing PAN is challenging, as it is not possible to make a diagnosis through clinical examination or serological testing alone, and atypical presentations occur 3–5. Diagnosis is dependent on a combination of clinical, radiological and histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Повышенное артериальное давление, абдоминальная ишемия, инсульты, ишемическая болезнь сердца, легочные васкулиты и др. характеризуются тяжелым течением вследствие поражения почек и имеют высокую летальность [5,6] В патогенезе узелкового полиартериита основную роль играет активация иммунного процесса и накопление лейкоцитов, связанных с иммунными комплексами. Иммунокомплексное воспаление развивается в стенках мелких и средних артерий.…”
Section: Introductionunclassified